Measuring Dyed Fiber Color with MSFU-K Microscope Spectrophotometer: Methodology Validation - Galina I. Bebeshko; Irina P. Lyubetskaya; Lidiya P. Brunova; Marina A. Khanukaeva; Georgii G. Omel'yanyuk (Теория и практика судебной экспертизы)
This work is part of a series of efforts towards validation of methods used in forensic fiber analysis. These efforts address current needs for accreditation of forensic laboratories and quality control in operations.The qualitative testing methodology consists of obtaining absorption spectra with the microscope spectrophotometer MSFU-K and comparing the spectral characteristics of color in fiber samples. The expert determines whether the textile fibers submitted for analysis match in color or not, depending on the results of spectral comparison.The proposed validation experiment algorithm is designed for evaluating uncertainty in optical density measurements and the level of expert competence.In this case uncertainty corresponds to reproducibility standard deviation. To evaluate uncertainty, two operators took readings of absorption spectra of dyed fibers independently in the course of three days, and measured optical density at maximum and minimum absorption wavelengths. To evaluate repeatability, 5 spectra were obtained in a row on each of the three days.The testing was conducted using three samples of polyacrylonitrile (PAN) fibers. Key characteristic points in the samples’ absorption spectra covered a wide range of wavelengths in the visible spectrum. Measurements were taken using the MSFU-K microspectrophotometer, which consists of a microscope with a spectrophotometric add-on unit.Statistical analysis of measurement data demonstrated uncertainty levels between 7,1 % and 22,1 %. Uncertainty values below 30 % are indicative of quantitative measurements and insignificant variance of optical density values, which corresponds to high reproducibility of spectra and allows the expert to make statistically reliable match/non-match conclusions on the color of compared fibers.Expert competence was assessed based on «blind» test results. The experts had to determine which of the three samples were colored with the same dye. Each of the two experts was provided with 3 visually identical samples that were colored with different dyes. The experts were asked to distinguish between fibers treated with the same dye. When analyzing obtained spectra, both experts correctly identified same-color fibers based on matching color spectral characteristics.Positive validation results suggest that the MSFU-K microscope spectrophotometer can be successfully used in forensic fiber analysis for measuring the color of dyed fibers.